2022
DOI: 10.1108/rausp-02-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of workplace safety on employee retention using sequential mediation: evidence from the health-care sector

Abstract: Purpose This study aims to examine the impact of workplace safety (WPS) on employee retention (ER) in the health-care sector in Azad Jammu and Kashmir (AJ&K), Pakistan. At the same time, a mediation relationship through job satisfaction (JS) and employee loyalty (EL) was also tested. Design/methodology/approach Structured questionnaires were used to collect the data from 300 doctors, using purposive sampling technique analysed using partial least squares (Smart-PLS 3). Findings This study’s findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
(77 reference statements)
0
3
0
3
Order By: Relevance
“…Partial Least square (PLS) is suitable for testing structural and measurement models simultaneously to obtain a thorough analysis for intent relationships (Aman-Ullah, Aziz, & Ibrahim, 2021a; Aman-Ullah, Aziz, Ibrahim, Mehmood, & Abbas, 2021b, Aman-Ullah et al. , 2022a, b). To perform the PLS, an algorithm involving factor loadings, composite reliability and average extracted variance was applied whereas the value of R 2 and t-statistics were calculated through bootstrapping (Henseler et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial Least square (PLS) is suitable for testing structural and measurement models simultaneously to obtain a thorough analysis for intent relationships (Aman-Ullah, Aziz, & Ibrahim, 2021a; Aman-Ullah, Aziz, Ibrahim, Mehmood, & Abbas, 2021b, Aman-Ullah et al. , 2022a, b). To perform the PLS, an algorithm involving factor loadings, composite reliability and average extracted variance was applied whereas the value of R 2 and t-statistics were calculated through bootstrapping (Henseler et al.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, past studies have shown a significant association of job satisfaction with employee retention and turnover intentions (Aman-Ullah et al. , 2022a, 2022b; Bangwal & Tiwari, 2019). Similarly, job satisfaction has been reported to be significantly associated with compensation (Muguongo et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lingkungan kerja digambarkan sebagai lingkungan fisik, misalnya kebisingan, getaran, ventilasi dan suhu dll (Hafeez et al, 2022). Karyawan lebih mungkin untuk tinggal di perusahaan di mana suasana kerja yang diharapkan dipertahankan (Majid et al, 2014), dan dengan situasi kerja yang tidak memadai seperti pencahayaan yang buruk, perabotan yang tidak memuaskan, dll, karyawan enggan bekerja untuk dalam jangka waktu yang lebih lama (Aman- Ullah et al, 2022). Fokus utama organisasi tetap pada menawarkan pekerjaan yang lebih baik kepada karyawan serta mempertahankan mereka dengan menyediakan lingkungan kerja yang baik (Mayer et al, 2022b).…”
Section: Pendahuluanunclassified
“…Hal demikian bermakna bahwa diperlukannya keselamatan tempat kerja dan budaya aman yang tinggi dalam lingkungan perusahaan agar karyawan merasa diperhatikan, nyaman, dan memiliki rasa tanggung jawab serta memiliki pada perusahaan yang tinggi. Selain itu, tidak adanya keselamatan berdampak besar pada sikap dan perilaku karyawan, seperti kepuasan kerja, loyalitas karyawan, dan retensi karyawan (Aman- Ullah et al, 2022).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation